Effect of arch pad on ankle joint pronation during gait with different treadmill speeds - Kim, H. Y.; Sakurai, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to evaluate the effect of an arch pad on changes of threedimensional (3D) ankle joint kinematics while walking and running at three different treadmill speeds (5km/h, 7km/h, and 10km/h). Six healthy male subjects were tested. Walking (5km/h) and running (7km/h,10km/h) motions with two shoe conditions (with and without medical arch pad) on a treadmill were analyzed by a motion capture system (Vicon-MX, 10 cameras, 250Hz). The effects of medial arch pad on foot eversion motion were found to be effective with all treadmill speeds. Additionally, the interaction between shoe conditions and gait speeds on eversion angle was significant(p<0.05). Consequently, it will be important to choose an arch pad of an appropriate size and material in order for individuals to reduce pain and to prevent running injuries.